2015
DOI: 10.4269/ajtmh.14-0344
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Blastocystis hominis and Other Protozoan Parasites in Soldiers Returning from Peacekeeping Missions

Abstract: Abstract. Blastocystis hominis is a common intestinal parasite found in humans living in poor sanitary conditions, living in tropical and subtropical climates, exposed to infected animals, or consuming contaminated food or water. The aim of this study was to determine the prevalence of B. hominis in Polish military personnel returning from peacekeeping missions in Iraq and Afghanistan. In total, 1,826 stool samples were examined. Gastrointestinal parasites were detected in 17% of the soldiers. The examined sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
2
15
1
Order By: Relevance
“…and Giardia lamblia) were identified in 56 % of the candidates patients. On the other hand, Duda, et al (2015) in Szczecin, Poland reported only single infection with B. hominis without co-existence of any other parasite in their samples.…”
Section: Discussionmentioning
confidence: 89%
“…and Giardia lamblia) were identified in 56 % of the candidates patients. On the other hand, Duda, et al (2015) in Szczecin, Poland reported only single infection with B. hominis without co-existence of any other parasite in their samples.…”
Section: Discussionmentioning
confidence: 89%
“…Transmission of Blastocystis is suggested to be by the fecal-oral route via contaminated water or food, with sources being both humans and animals. [28] Among helminthic infection Hook worm eggs were seen in 7 children indicating its prevalence to be 3.53%. Strongyloides stercoralis larvae were reported only in one child (0.50%) who was 14 years of age This patient did not have any history of immunosuppression and must have acquired the infection by walking bare feet in contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…In Afghan populations, overall prevalence of intestinal parasites as high as 39% has been noted [42], and commonly reported parasites include Giardia (15%-59%) [42][43][44] and Ascaris (20%-35%) [41]. Blastocystis was found in 15% of Polish soldiers returning from peacekeeping missions in both Afghanistan and Iraq; the infections were presumably contracted in these regions [45]. Several parasites may not cause symptoms; however, others have the potential to cause complications.…”
Section: Plos Medicinementioning
confidence: 99%